STRATEGI PENDAMPINGAN PEKERJA SOSIAL PADA PASIEN GANGGUAN JIWA DI RUMAH SAKIT JIWA GHRASIA - Lailatul Fitri (Jurnal Keperawatan Malang, 2019)
People with mental disorders in Indonesia reach more than 28 million people, with the category of mild mental disorders 11.6% of the population and 0.46% suffering from severe mental disorders or 46 per mile. Based on Basic Health Research, 14.1% of Indonesia's population experiences mental disorders from mild to severe, this condition is aggravated by various natural disasters that occur in almost all regions of Indonesia. Whereas according to WHO data in 2016, there were around 35 million people affected by depression, 60 million people affected by bipolar disorder, 21 million people affected by schizophrenia, and 47.5 million people affected by dementia. This study aims to find out various strategies for assisting social workers and knowing the supporting and inhibiting factors in carrying out a strategy to accompany social workers to mental patients in Grasia Mental Hospital because the strategies used will affect the success of a social worker. This research use desciptive qualitative approach. The results of the research obtained indicate that the strategy used by the social worker companion is first, increasing knowledge. Second, increase Third awareness, improve abilities and improve skills. Pendung and inhibiting factors in the strategy of mentoring social workers are in two aspects, namely patients and families. Keywords: mental disorders, social workers, mentoring strategies